The role of ethical climate on teachers’ wellbeing: relationship with psychophysical wellbeing and general health - Borrelli, Ivan; Angelini, Giacomo; Santoro, Paolo Emilio; Rossi, Maria Francesca; Gualano, Maria Rosaria; Moscato, Umberto; Fiorilli, Caterina (Frontiers in Public Health, 2025)
IntroductionPrevious studies have highlighted that the dissonance between workplace and personal ethics can lead to poorer mental health for employees. However, studies addressing the relationship between teachers’ wellbeing and workplace ethics are scarce. This study aims to investigate the relationship between ethical climate and mental and physical health outcomes in teachers.MethodsA cross-sectional study was conducted with 255 Italian teachers (88.63% female; mean age = 47.09 years). The study assessed the relationships among workplace ethics, general and mental health, and daytime sleepiness by descriptive analysis and multiple logistic regression models.ResultsThe study involved 255 Italian teachers recruited from schools of various grades (Female = 88.63%; Mean age = 47.09; SD = ±10.55). Most participants showcased “Good” (50.59%) or “Excellent” (42.75%) workplace ethics; 30.79% of participants reported anxiety, 27.06% depression, and 24.31% stress. Only 7.84% of participants scored over the cut-off for the general health questionnaire, and 26.67% reported daytime sleepiness. Using the logistic regression models, a significant correlation for workplace ethics was detected with the DASS-21 stress (p = 0.002) and depression (p = 0.011) subscales.ConclusionThe ethical climate in educational settings influences teachers’ mental health, particularly by reducing stress and depression. Enhancing the ethical environment in educational organizations could improve teacher wellbeing.